The Effects of Implementing Inquiry-Based 5Es Model on grade 9 EFL Students’ Interest and English Language Progress (2020)
ABSTRACT: This action research aimed to explore the effects of implementing the Inquiry Based Learning 5Es Model to enhance ninth graders’ interest and promote their language progress in the English class. It took place in a public school in Medellin, Colombia. The participants were 42 students, my two cooperating teachers, and myself. The pedagogical actions followed the five phases of the model: Engage, Explore, Explain, Elaborate, and Evaluate. Data collection instruments included preservice teacher and student surveys, teacher journal, and a class discussion. Findings suggest that implementing the 5Es Model helped to raise student’s interest and participation in class, and enhance their self- confidence to use English. However, implementing the model also posed challenges that hindered students from obtaining better results.